Conjunctival involvement in cicatricial and bullous pemphigoid: a clinical and immunopathological study. Issue 1 (January 1989) - Frith, P A; Venning, V A; Wojnarowska, F; Millard, P R; Bron, A J
Abstract : Patients with bullous pemphigoid were found to have significant ocular abnormalities. In a group of 18 patients one had conjunctival shrinkage, and 11 of 15 (73%) had positive linear direct immunofluorescence on conjunctival biopsy from a clinically uninvolved site. Our ocular findings in a group of 14 with cicatricial pemphigoid are also reported and compared with those from a control group of 20. Our findings suggest there is overlap between the pemphigoid groups and raise further questions about the pathogenicity of immunoreactants within the basement membrane zone. Bulbar conjunctival biopsy was simple and well tolerated, and the rate of immunofluorescence positivity of conjunctiva was twice that of skin in both pemphigoid groups.